Pregnancy rate in Bulgarian White milk goats with natural and synchronized estrus after artificial insemination by frozen semen during breeding season - Stanimir A. Yotov; Desislava V. Velislavova; Lora R. Dimova (Asian Pacific Journal of Reproduction, 2016)
Objective: To determine the pregnancy rate (PR) in goats with natural and synchronized estrus after artificial insemination (AI) by frozen semen during breeding season. Methods: The experiment was carried out with 89 Bulgarian White milk goats divided as follows: group I (n = 54) animals with natural estrus (NE), allocated in two subgroups treated with or not with GnRH after the last insemination and group II (n = 35) goats with synchronized estrus by intravaginal sponges and injection of PMSG after the sponges withdrawal. Both groups were also divided according to number AI – single or double. All animals in group I were inseminated by frozen semen after proved standing estrus as a part of goats received second insemination 8 h later. Single insemination in synchronized goats was done 48 and double at 48 and 56 h after the sponge removal. Ultrasound pregnancy diagnosis was performed on day 30 post insemination. Results: The pregnant animals in both subgroups with natural estrus and single AI (33.3% and 45.2%) were less than those (58.3%) after estrus synchronization (ES). The pregnancy rate in synchronized goats with double insemination was 63.6%, whereas in animals with natural estrus varied from 40 to 50%. Overall pregnancy rate in group I (60%) was significantly (P < 0.05) higher than (37%) in goats without GnRH treatment. Conclusion: The goats with natural estrus and GnRH treatment tend to enhance pregnancy rate after double artificial insemination 8 h apart. The insemination number has no significant impact on pregnancy rate in synchronized goats as the overall pregnancy rate is better than in animals with natural estrus without GnRH administration.